Pendidikan Anti Korupsi bagi Generasi Muda SMKN 1 Jrengik “Sebagai Upaya Pencegahan Korupsi Sejak Dini” - Faisol Faisol (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
This Community Service aims to provide knowledge to students of SMKN 1 Jrengik to know things related to corruption from an early age so that they can create a young generation who are aware and understand the dangers of corruption, and are able to identify forms of corruption, and know the sanctions. - sanctions that will be received for corruption. To give birth to a young generation who are moral and can form role models so that the younger generation is not infected with corruption from an early age to form an anti-corruption character from an early age, especially for students. The method used in this PKM is lectures and questions and answers with resource persons, apart from that, the delivery of this training is carried out by providing simple examples that occur related to criminal acts of corruption and models for preventing corruption from an early age. So that this anti-corruption education can be useful for students to be aware of anti-corruption, especially at SMKN 1 Jrengik and it is hoped that it can be applied by students in the surrounding environment.